Role of Metaphor in Forming Military Discourse Terminology (by Material of English Periodicals) - K. A. Degtyarenko (Научный диалог)
The article is devoted to the study of metaphor as a cognitive mechanism for the creation of a new term, based on the integration and reinvention of knowledge in the light of background information and new field of special knowledge. The material is the English articles devoted to the military. The important role of the process of metaphorization in the formation of modern English terminology of military discourse is established. Appeal to the study of military terminology is important due to its intensive development in conditions of modern technological progress and significance of issues related to the military sphere. The main areas-sources of lexical borrowings used for the formation of metaphorical terms of military discourse are identified. Actualized indications of borrowed lexical units are considered. The most productive thematic areas of the metaphorical terms formation are revealed. The unevenness of metaphorical nomination in thematic groups reflects the dynamics of the emergence of new concepts within the thematic groups, and, consequently, the value relevance of the thematic groups for the military team. It is proved that formation of military terminology metaphor is based on the principles of anthropometrical, consistency, selectivity and relevance, giving an idea of the system of value orientations of specialist in studied area.